HYDRAULIC AND TECHNICAL CHARACTERIZATION OF DRIPPERS NONSELF-COMPENSATING - Dalri, Alexandre Barcellos [UNESP]; Baca Garcia, Carlos Jesus; Palaretti, Luiz Fabiano [UNESP]; Zanini, Jose Renato [UNESP]; Faria, Rogerio Teixeira de [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2015)
This study aims to characterize and evaluate seven models of turbulent flow nonself-compensating drippers available in the Brazilian market. The characterization of the emitters followed the procedures of the standards NBR ISO 9261. The experiment was conducted at UNESP University Estadual Paulista, Botucatu Campus, Department of Rural Engineering. For the execution of the test one randomly took from each coil, segments containing 25 emitters. In the evaluation of hydraulic and technical characteristics of emitters were determined the following parameters: coefficient of manufacturing variation, coefficients of the characteristic equation of the emitter, thickness of the tube wall, internal diameter, spacing between emitters, water pressure resistance at ambient temperature and 40 degrees C, the tensile strength of the tube with a tension of 160 N and 180 N, and premature aging testing. The analysis of the drip tapes showed a coefficient of manufacturing variation of less than 0.056 for all emitters. The exponents (m) of the equation pressure versus flow rate ranged from 0.431 to 0.575, classifying them as nonself-compensating. About the wall thickness, the internal diameter of the drip tapes and the spacing between emitters were found out that all measured values are within the required standard. From the results obtained, it can be stated that all products tested and available in the Brazilian market showed satisfactory performance and quality.
Keywords: Evaluation; Drip; NBR ISO 9261